Linking Logistics Partnerships and Supply Chain Integration to Distribution Performance: Evidence fro the Marine Product Industry in West Sumatra - Obyn Imhart Pumpente; Yuminarti , Umi; Bakri , Muhammad Djaya (CV. HEI PUBLISHING INDONESIA, 2025)
The marine product sector in West Sumatra shows significant export potential but faces challenges in distribution efficiency and quality. Logistics partnerships and supply chain integration are key drivers for improving performance across industries. This study examines the relationship between logistics partnerships and supply chain integration and their effects on distribution performance of marine commodities in West Sumatra. Using a quantitative approach and Structural Equation Modeling–Partial Least Squares (SEM-PLS), official secondary data from BPS West Sumatra, Pelindo Teluk Bayur, KKP, and national export statistics over four years were analyzed. The results indicate a significant positive effect of logistics partnerships on supply chain integration, which in turn significantly enhances distribution performance by reducing lead time and increasing export volume and value. The study concludes that optimizing marine product distribution in West Sumatra requires strengthening strategic logistics partnerships and deeper integration of processes among all stakeholders from capture and cultivation to export port.